Some aspects of bill morphology in relation to ecology in the great tit Parus major - Gosler, A; Gosler, Andrew (1987)
Ornithologists have long recognised a relationship between bill morphology and the ecological niche between species. This general relationship was described for the genus Parus over 30 years ago. Recently, the long-held assumption that the relationship was adaptive in this genus (and in the Great tit in particular) has been questioned. This study examines the evidence that bill variation is adaptive (ie: contributes to fitness) in the marked Great tit population of Wytham Wood, Oxford, U.K. Over 1000 full grown individuals were measured (mean retrap rate of 1.67 per bird) between May 1982 and July 1985. The short-term repeatability (which inversely measures observer error) for all measurements taken was over 90%. Bill characters were more variable than any other linear measurements taken. This was because bill characters varied strongly with sex (independent of sex-differences in body size) and season (within birds) and in males in spring, varied with age also. Long-term repeatability estimates were significantly lower than short-term, indicating that bill size changed between seasons (within birds). These results, together with a seasonal change in the heritability estimates of bill characters (which were greater in summer than in winter) indicated that they were strongly influenced by variation in the environment and that this was especially true in winter. Changes in adult bill size in spring were due to active bill moult. This has not been described previously in a passerine. The occurrence of moult was related to the bill size and behaviour of the bird and it was suggested that the bird might exercise some active control over the bill size. Bill depth in 15 day-old nestlings was unimodal. Most of the explainable variation in bill depth at this age was due to variation in the growth environment. By four months of age, bill depth was strongly sexually dimorphic. Males had shorter but deeper bills than females. Evidence that this may have resulted from differential directional selection for bill depth itself is presented. In general, there was little evidence for natural selection of or for bill characters in the birds once fully grown, but when observed, it tended to affect sub-dominant classes of birds. In winter, bill variation corresponded closely with variation in foraging niche among individuals. A series of laboratory experiments were carried out with captive birds to test their skill at handling different foods in relation to bill size. The differences in bill size and shape among age and sex classes observed in the field in relation to differences in niche corresponded with those expected from the optimal bill sizes (in terms of feeding efficiency) shown by the laboratory experiments. Other evidence was described to support the view that bill size and feeding efficiency were correlated. It was suggested that in winter, bill differences among age and sex classes allowed niche segregation within the population, so reducing intraspecific competition. In some summers, prey size correlated with bill length. In those summers, the mean fledging weight of chicks whose parents differed in bill length tended to be greater than that of chicks with more similar parents. It was suggested that this was because parents with different bill lengths competed less for food and so delivered more food to the nest. The study concluded that bill size was highly adaptive in that it was related to fitness (in the broad sense) or to some correlate of fitness. The results are considered in terms of existing niche theory and especially of "character displacement" and the "variable niche hypothesis".